2016
DOI: 10.1007/s10461-016-1346-5
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Published Respondent-Driven Sampling Surveys Collecting Behavioral and Biologic Data

Abstract: Acknowledgments:We would like to thank Kate Orroth for conducting the literature search for the STROBE-RDS Guidelines and allowing us to use it for this analysis. Abstract word count: 160Word count: 3060 ABSTRACTReporting key details of respondent-driven sampling (RDS) survey implementation and analysis is essential for assessing the quality of RDS surveys. RDS is both a recruitment and analytic method and, as such, it is important to adequately describe both aspects in publications. We extracted data from pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 146 publications
(54 reference statements)
2
64
0
2
Order By: Relevance
“…RDS is a chain-link sampling method that permits participants to recruit their acquaintances and uses a mathematical model to adjust for this method of recruitment [16][17][18] . RDS is used in hundreds of surveys [19][20][21] around the world and was recently identified as a major contribution to social, behavioral and economic research by the U.S. National Academies of Sciences 22 . RESUMO: Introdução: Este artigo detalha os métodos utilizados na segunda Pesquisa Nacional de Vigilância Biológica e Comportamental (BBSS) do HIV, sífilis e hepatite B e C entre os homens que fazem sexo com homens no Brasil.…”
Section: Introductionmentioning
confidence: 99%
“…RDS is a chain-link sampling method that permits participants to recruit their acquaintances and uses a mathematical model to adjust for this method of recruitment [16][17][18] . RDS is used in hundreds of surveys [19][20][21] around the world and was recently identified as a major contribution to social, behavioral and economic research by the U.S. National Academies of Sciences 22 . RESUMO: Introdução: Este artigo detalha os métodos utilizados na segunda Pesquisa Nacional de Vigilância Biológica e Comportamental (BBSS) do HIV, sífilis e hepatite B e C entre os homens que fazem sexo com homens no Brasil.…”
Section: Introductionmentioning
confidence: 99%
“…2 A review of peer-reviewed studies collecting biological specimens counted 222 RDS surveys as of 2013 (Johnston et al 2016). A review of RDS for biological and behavioral surveillance of populations at risk for HIV counted 123 surveys as of 2007 (Malekinejad et al 2008).…”
Section: Figurementioning
confidence: 99%
“…In a review of RDS surveys, the WHO (2013) determined the median number of seeds was eight, and that an average of 1.6 were unsuccessful. 27 The average sample size and number of waves in a review of RDS biological surveys were 325 and 9, respectively (Johnston et al 2016). 28 The sample was smaller than the target size of 313, which was estimated as n ¼ pð1ÀpÞ varðyÞ DE where p is the expected proportion, var(y)is the variance, and DE is design effect, calculated with a conservative proportion estimate of 0.50, standard error of 0.04, and a design effect of 2.…”
Section: Searched Proquest's Worldwide Political Sciencementioning
confidence: 99%
“…RDS has been widely adopted to estimate the prevalence of disease or risk behaviours within high risk hard-to-reach human populations, including PWID, sex workers and men who have sex with men. It has been used in hundreds of studies around the world (Johnston et al, 2008(Johnston et al, , 2016Montealegre et al, 2013), for surveys of biological behavioural surveillance funded by the Global Fund to monitor HIV prevalence, to assess risk and programme coverage and to measure trends over time (Lansky et al, 2007). Despite its wide use in settings of public health importance, the statistical properties and optimal inferential strategies for data resulting from RDS still require much additional study.…”
Section: Respondent-driven Sampling Backgroundmentioning
confidence: 99%
“…Several RDS prevalence estimators have been proposed and implemented (Heckathorn, 1997(Heckathorn, , 2002Salganik and Heckathorn, 2004;Volz and Heckathorn, 2008;Gile, 2011;Gile and Handcock, 2015); however, it has been demonstrated that no one estimator is superior in all cases (Tomas and Gile, 2011). We briefly review the three most commonly implemented estimators of μ: the Volz-Heckathorn (VH) estimator, the successive sampling (SS) estimator, and the Salganik-Heckathorn (SH) estimator, and their relationships to the estimator proposed (Johnston et al, 2016). The VH and SS estimators estimate the probability of observing individuals based on their degree and use this probability to perform inverse probability weighting.…”
Section: Respondent-driven Sampling Prevalence Estimatorsmentioning
confidence: 99%